The Partisan Gap in Leader Support and Attitude Polarization in a Campaign Environment: The Cases of Germany and Italy. (11th July 2016) - Barisione, Mauro
Abstract: An under-investigated yet exemplary form of political polarization in the mass public is the so-called "partisan gap in leader support." By providing an original analysis of two non-U.S. contexts—the 2013 German and Italian general elections—we show that the simple act of voting for a party involves partisan-motivated reasoning, that is, evaluations of party leaders that are clearly sorted along party lines (in-party leader vs. all out-party leaders). This effect is moderated by voters' degree of political interest and the time of their vote decision. Moreover, it tends to increase during election campaigns. These trends are more pronounced in political contexts with greater systemic polarization.